2021
DOI: 10.1007/s10856-021-06511-z
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane derived from castor oil monoacylglyceride (Ricinus communis) for bone defects reconstruction: characterization and in vivo testing

Abstract: Biomaterials used in tissue regeneration processes represent a promising option for the versatility of its physical and chemical characteristics, allowing for assisting or speeding up the repair process stages. This research has characterized a polyurethane produced from castor oil monoacylglyceride (Ricinus communis L) and tested its effect on reconstructing bone defects in rat calvaria, comparing it with commercial castor oil polyurethane. The characterizations of the synthesized polyurethane have been perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…We concluded that 3D printed PU scaffolds with shape memory properties, biodegradability, and osteogenic effect may be employed by the minimally invasive surgical procedures as customized bone substitutes. 122 Morais et al 123 synthesized polyurethane from castor oil monoacylglyceride (MAG) and applied it for bone defect reconstruction in rats. The surgery was performed on three groups, namely the untreated group (UG), control group with Poliquil castor polyurethane (PCP), and synthesized castor polyurethane group UFPI(CPU).…”
Section: Synthesis and Structure Of Pus (Different Types Of Pus Being...mentioning
confidence: 99%
“…We concluded that 3D printed PU scaffolds with shape memory properties, biodegradability, and osteogenic effect may be employed by the minimally invasive surgical procedures as customized bone substitutes. 122 Morais et al 123 synthesized polyurethane from castor oil monoacylglyceride (MAG) and applied it for bone defect reconstruction in rats. The surgery was performed on three groups, namely the untreated group (UG), control group with Poliquil castor polyurethane (PCP), and synthesized castor polyurethane group UFPI(CPU).…”
Section: Synthesis and Structure Of Pus (Different Types Of Pus Being...mentioning
confidence: 99%
“…The spectra obtained by Fourirer transform infrared spectroscopy were compatible with what has already been reported in the literature, confirming the standardization of the scaffolds production. In the thermal analysis, the biomaterial also behaved in a predicted way, showing thermal degradation in three different stages, starting at 180ºC, going through 280ºC and ending at 380ºC with the greatest loss of mass (57%), according to previous studies [7][8][9] .…”
Section: Resultsmentioning
confidence: 64%
“…The scaffolds were found from castor oil monoglyceride and characterized as described in previous studies [7][8][9] . The pure Castor oil was commercially acquired.…”
Section: Production and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The slower re-absorption process is one of the benefits of Ricinus Communis polythene. Ricinus Communis oil does not contain a lot of medicinal properties such as anticonvulsant, anti-inflammatory, antiasthmatic, laxative, purgative, antibacterial, and bone regeneration; hence it is widely used across the world [37][38][39] .…”
Section: Larvicidal and Mosquitocidalmentioning
confidence: 99%